2012
DOI: 10.1093/aje/kws139
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Coronary Heart Disease: A Systematic Review and Meta-Analysis

Abstract: The authors aggregated the results of observational studies examining the association between long working hours and coronary heart disease (CHD). Data sources used were MEDLINE (through January 19, 2011) and Web of Science (through March 14, 2011). Two investigators independently extracted results from eligible studies. Heterogeneity between the studies was assessed using the I2 statistic, and the possibility of publication bias was assessed using the funnel plot and Egger's test for small-study effects. Twel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
199
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(217 citation statements)
references
References 77 publications
8
199
0
2
Order By: Relevance
“…Working long hours (>55 hours on the average week) is also related to a ∼40% excess risk of incident CHD (113). Evidence on the association of workplace stress with stroke is scarce and inconsistent (51).…”
Section: Figurementioning
confidence: 99%
“…Working long hours (>55 hours on the average week) is also related to a ∼40% excess risk of incident CHD (113). Evidence on the association of workplace stress with stroke is scarce and inconsistent (51).…”
Section: Figurementioning
confidence: 99%
“…Associations between working conditions (i.e. long working hours, language problems, lack of safety training) and health problems, including accidents at work are well documented in the literature (3,(51)(52)(53).…”
Section: Perceived Health Risksmentioning
confidence: 99%
“…A number of studies have shown that longer working hours are associated with a range of adverse health consequences such as higher prevalence of stroke [1], coronary heart disease [2], metabolic disorders [3] and mental disorders [4]. Shorter as well as longer sleep duration has also been shown to increase the prevalence of several chronic illnesses, poorer self-rated health and lower quality of life [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%